Aerosol Remote Sensing - Lenoble, Jacqueline; Remer, Lorraine; Tanre, Didier; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book gives a much needed explanation of the basic physical principles of radiative transfer and remote sensing, and presents all the instruments and retrieval algorithms in a homogenous manner. The editors provide, for the first time, an easy path from theory to practical algorithms in one easily accessible volume, making the connection between theoretical radiative transfer and individual practical solutions to retrieve aerosol information from remote sensing, and providing the specifics and intercomparison of all current and historical retrieval methods.
Absorption and Scattering by Molecules and Aerosols -- Radiative Transfer in the Earth's Atmosphere -- Direct Observation of the Sun -- Observation of the Difuse Solar Radiation and the Influence of Aerosols: Determination of Aerosol Optical Properties from Direct and Inverse Methods -- Passive Shortwave Remote Sensing from the Ground -- Shortwave Remote Sensing from Space -- Major Recent or Present Instruments for Shortwave Remote Sensing -- Longwave Passive Remote Sensing -- Active Lidar Remote Sensing -- Results -- The Present Situation -- Plans for Future Research.
Keywords: Geography; Remote sensing; Climatic changes; Earth Sciences; Remote Sensing/Photogrammetry.; Geophysics and Environmental Physics; Climate Change